NILAI NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SIRAH NABAWIYAH - Yosep Heristyo Endro Baruno; Rahima Sikumbang Sarmadi; Evi Damayani Nasution (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
Character education is one of the main focuses in today’s education world, considering the importance of forming good character for students. In the context of Islamic education, learning the sirah nabawiyah has a significant role in shaping the character of students. Sirah nabawiyah, which is a record of the life of the Prophet Muhammad SAW, not only functions as a source of history, but also as a guideline in forming good morals and behavior. This study aims to identify and analyze the values of character education contained in the learning of sirah nabawiyah. The methodology used is a literature study by analyzing various sources such as books, scientific articles, and relevant educational documents. The results of this study indicate that learning sirah nabawiyah not only conveys information about the life of the Prophet Muhammad SAW, but also instills character values such as honesty, discipline, compassion, and responsibility. These values are expected to shape better student character and support moral and ethical development in everyday life.